Alumina-encapsulated vaccine formulation with improved thermostability and immunogenicity. Issue 38 (21st April 2016) - Zhou, Hangyu; Wang, Guangchuan; Li, Xiao-Feng; Li, Yaling; Zhu, Shun-Ya; Qin, Cheng-Feng; Tang, Ruikang
Abstract : Encapsulation of vaccines within alumina, a FDA approved inorganic adjuvant, can produce a more robust vaccine formulation with improved thermostability and enhanced immunogenicity. Abstract : Developing vaccine formulations with excellent thermostability and immunogenicity remains a great challenge. By in situ encapsulating a live-attenuated strain of human enterovirus 71 (EV71) in alumina, we obtained a robust vaccine formulation named EV71@NanoAlum, which features significantly enhanced thermostability and immunogenicity. This attempt follows a material-based tactic for vaccine improvement.